Political rhetoric, identities, and dominant gender representations: hegemonic masculinity in service of pro-austerity rhetoric in Greek political discourse - Petrogiannis, Vasileios; Freidenvall, Lenita (Norma : International Journal for Masculinity Studies, 2022)
This article examines the construction of hegemonic masculinity in Greek political discourse, by analysing minutes from the Greek Parliament at the height of the economic crisis in 2010-2012. Based on Connell's concept of hegemonic masculinity and the application of a discursive approach inspired by Laclau and Mouffe ([1985]. Hegemony and socialist strategy: Towards a radical democratic politics. London: Verso), the article asks: (1) which discourses constituted the rhetoric of Greek elite politicians regarding economic policies during the crisis and (2) which hegemonic concepts of masculinity and femininity did Greek elite politicians elaborate upon and discursively position themselves in. It also reflects on the implications of the gendered speeches of these elite politicians. The article shows how the rhetoric of elite politicians includes different identities normatively related to manhood. The article argues that the construction of these gender dominant gender representations in the political discourse has severe implications in terms of functioning as a means of justification of austerity measures in Greek economy with negative consequences for politics and society. It is also argued that by adopting elements of hegemonic masculinity, Greek elite politicians contribute to creating an image of a powerful man to whom citizens should adhere, hence reproducing the male (white and heterosexual) norm.